Effects of Early Marriage on the Health of Female Adolescents - Adhikari, Ram Prasad; Adhikari, Bhashkar Chandra; Oli, Menuka; Rai, Junu; Kumari, Aarati; Devkota, Samrachana; Humagain, Niruta (International Research Journal of MMC, 2023)
The main aim of the study was to analyze the prevalence of early marriage and examine its effects on the health of adolescent mothers. The research was conducted at BanakariyaTol of Manahari rural municipality, Makawanpurin the year of 2023. Simple random sampling technique (lottery method) was applied to select 97 respondents out of 235 households. Chi-square and Fisher's Exact Test was used to analyse the data. It is found that educational attainment among locale was significantly associated (p-value=0.01) with early marriage practices. Apart from educational attainment, other variables are unassociated. Significant association was found between age of marriage and effects on health while bearing child in early ages χ2 (2, N = 97) = 12.908, p < .001.Low level of education as well as the socio-cultural practices of the people were the main factors for high preference and prevalence of early marriage among female adolescents. The concern people, government and other agencies should formulate the suitable plan and policies to create awareness towards the reproductive health problems of adolescent mothers as well as to protect their reproductive health rights and uplift them for proper decision-making capacity and self-dependency.